Exploration evoked by the environment is balanced by the need to perform in cricket spin bowling. (November 2021) - Crowther, Rian H.; Gorman, Adam D.; Renshaw, Ian; Spratford, Wayne A.; Sayers, Mark G.
Abstract: In the theory of ecological dynamics, adaptive responses emerge through exploration when an individual interacts with their environment. This study investigates how when competing, the environment guides perceptual-motor exploration that is balanced by the need to meet performance requirements. To understand this, eight emerging expert cricket spin bowlers aged 21 ± 3 years competed in three small-sided simulated practice matches where pitch conditions were manipulated to present familiar and unfamiliar environmental pitch constraints. It was hypothesized that bowlers would explore the unfamiliar pitch by searching for an action mode that allowed them to best exploit the conditions to achieve a successful outcome (e.g., take a wicket) while simultaneously attempting to satisfy the immediate performance requirements (e.g., limit runs per over). A mixed methodology was used to first identify the perceptions and intentions of the bowlers (dimensions, themes, and action modes), followed by analysis of the resultant action characteristics (delivery speed, spin rate, and pitching position) and performance outcomes (economy rate, strike rate, and bowling average). Overall, when competing on the familiar pitch, the bowlers reported primarily attuning to task constraints (75%). In contrast, when bowling on the unfamiliar pitch, all bowlers reported that their attention was more focused upon picking up key affordances related to environmental pitch constraints (100%). The majority of bowlers indicated that they bowled differently on the unfamiliar pitch by using more "side-spin" and less "over-spin". Interestingly, it was not until the second performance on this pitch that execution variables significantly changed. Despite these changes, bowlers continued to pay attention to the opposing batters' strategies throughout all three practice matches. The consistency of this response can be explained by an overarching strategy for all types of bowling in cricket that is more closely linked to the ongoing individual-opponent interaction. That is, the bowlers must perform and 'stay in the game' whilst simultaneously adapting to any environmental changes. Therefore, demonstrating the need to continually satisfy the immediate performance requirements to afford the opportunity to explore new affordances in the environment that may offer exploitation. Highlights: Constraints, attunement, action modes, execution and outcome impact adaptability. An unfamiliar environmental constraint impacts match play strategies. Environmental adaptation and therefor exploitation first requires exploration. Environmental exploration is balanced by the need to simultaneously perform. Local bespoke pitch conditions offer practice of alternate match play strategies.